Wegetarianizm we współczesnych religiach światowych. Zarys problemu - Jedlecka, Wioletta (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
A purpose of this article is expressing the very interesting issues concerning the ritual sphere of big religions of world. In particular it concerns diet provisions referring to food of the animal origin. Principles of the religion determine in this situation, what kind of food is allowed to the consumption. Is a question, whether it is possible to separate the religion from the vegetarianism? Religions differ from themselves. However they agree as for the need for the moral behaviour and ethic. A charity and sympathizing towards the poor one are core values. These values are valued highly by all religions of world.